(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The text situates study as a speculative practice of creation and disassembly of bodies, in favor of ways of living that counter the reified insensitivity of the Anthropocene. To this end, it proposes studying as a mode of entanglement and sociality between humans and others-than-humans, drawing on a research-creation approach concerned with the dynamics of the emergence of apparitions: fabulated creatures that, born from the relationship between bodies and/or vestiges, emerge accompanied by stories that enable us to think and experiment with other ways of existing, capable of confronting the ruins of our times.